2016
DOI: 10.1542/peds.2016-2148
|View full text |Cite
|
Sign up to set email alerts
|

Sports Specialization and Intensive Training in Young Athletes

Abstract: Sports specialization is becoming the norm in youth sports for a variety of reasons. When sports specialization occurs too early, detrimental effects may occur, both physically and psychologically. If the timing is correct and sports specialization is performed under the correct conditions, the athlete may be successful in reaching specific goals. Young athletes who train intensively, whether specialized or not, can also be at risk of adverse effects on the mind and body. The purpose of this clinical report is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
277
2
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(302 citation statements)
references
References 60 publications
1
277
2
7
Order By: Relevance
“…Additionally, at the collegiate level, practice and training are more likely to occur year-round, though specialization is increasing at the high school level. 18,19 With this yearround practice and training schedule, the overall work load is greater, possibly increasing the risk of overuse injuries and injuries due to fatigue. 20 The proportion of injuries that were due to no contact was larger in college than in high school, though the proportion due to an overuse mechanism was similar in high school and college.…”
Section: Comparisons Between and Within High School Girls' And Collegmentioning
confidence: 99%
“…Additionally, at the collegiate level, practice and training are more likely to occur year-round, though specialization is increasing at the high school level. 18,19 With this yearround practice and training schedule, the overall work load is greater, possibly increasing the risk of overuse injuries and injuries due to fatigue. 20 The proportion of injuries that were due to no contact was larger in college than in high school, though the proportion due to an overuse mechanism was similar in high school and college.…”
Section: Comparisons Between and Within High School Girls' And Collegmentioning
confidence: 99%
“…In college, practice and training are more likely to occur year round, though specialization is increasing in high school. 20,21 Year-round practice and training may increase overuse injuries and injuries due to fatigue. 22,23 In collegiate men's baseball, 25% of injuries were due to an overuse/chronic mechanism and 44% were due to no contact, as compared with 18% due to overuse/chronic and 31% due to no contact in high school boys' baseball.…”
Section: Comparisons Between and Within High School Boys' And Collegimentioning
confidence: 99%
“…However, whether the early involvement in the main sport (i.e., early specialization) will be safe and allow further performance improvements in later stages of long-term athlete development still an open question that needs to be addressed in future long-term studies. However, it has frequently been reported that early specialization may lead to negative consequences at later stages of long-term athlete development (e.g., higher dropouts and risk of injuries) [8][9][10][11][12][13]44]. Accordingly, this pathway was deemed potentially detrimental when adopted at early stages of long-term athlete development.…”
Section: Muscle Strength/power Dynamic Balance and Sport-specific Pmentioning
confidence: 99%
“…In other words, different components of physical fitness should specifically be promoted during the early stages of long-term athlete development while sport-specific skills should be developed during the later stages [10]. In addition, it seems that early specialization is associated with a greater risk of sustaining acute and/or chronic injuries and dropouts [8,[11][12][13] while fewer injuries appear to occur with diversification (i.e., late specialization) [13,14]. There is also research available that suggests an increased likelihood of becoming an elite athlete on an international level when following the diversification pathway [9].…”
Section: Introductionmentioning
confidence: 99%